INTEGRATION OF ISLAMIC EDUCATIONAL VALUES IN THE JARANAN TRADITION (SYNERGY BETWEEN CULTURE AND SPIRITUALITY OF JARANAN PORONG BANYUWANGI ) - Ahmad Saiq Alifi; Imam Turmudi; Lailatul Usriyah (International Journal of Teaching and Learning, 2025)
Jaranan Lintang Jaya Kusuma art is a traditional Javanese art that combines dance, music, and spirituality. Each performance conveys cultural values and life philosophies. Dance movements contain spiritual meaning, such as a symbol of surrender to God. Before the performance, a prayer ritual is usually performed. The dances performed include Barong Prejeng, Leak, Pitik, and Possession, which have symbolic meanings. Jaranan is also a means of preaching and preserving culture. In this study, the approach used in this study is a qualitative approach. The qualitative approach was chosen because this study aims to determine the integration of Islamic educational values in the jaranan tradition (synergy between culture and spiritual jaranan porong banyuwangi). While the type of research uses descriptive type. Descriptive research is research to examine the status of a group of people, an object, a condition, a system of thought or an event in the present . Research Results Jaranan Lintang Jaya Kusuma is a traditional art from Porong Banyuwangi, East Java, which combines Javanese culture with Islamic values. This performance contains elements of dance, music, and spirituality, often involving trance conditions. Before performing, prayers and verses of the Qur'an are read to ask for blessings. Jaranan teaches morals, self-control, tawakal, and purity of intention, and functions as a means of moral and spiritual education for the community.